2021
DOI: 10.3390/ijerph181910059
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Safe Dental Care: A Systematic Review of Clinical Practice Guidelines in the First Year of the COVID-19 Pandemic

Abstract: In the context of a pandemic, the rapid development of clinical practice guidelines (CPGs) is critical to guide dental staff towards the safe provision of dental care; detailed knowledge of the recommendations will help to achieve the intended results. We carried out a systematic review of the recommendations in clinical practice guidelines (CPGs) on the provision of dental care issued during the first year of the COVID-19 pandemic. A systematic database search was performed in MEDLINE, EMBASE, LILACS, Epistem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…Oral health care services were negatively influenced, both because the activity in the dental clinics were forced to be reorganized in order to limit the spread of the virus [ 6 , 7 , 8 , 9 , 10 , 11 ], but also because a great part of the dentists and periodontists were under significant psychological pressure and distress levels [ 12 , 13 , 14 ]. Months after reopening the dental offices, studies showed that the probability of COVID-19 contamination within dental clinics was very low [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral health care services were negatively influenced, both because the activity in the dental clinics were forced to be reorganized in order to limit the spread of the virus [ 6 , 7 , 8 , 9 , 10 , 11 ], but also because a great part of the dentists and periodontists were under significant psychological pressure and distress levels [ 12 , 13 , 14 ]. Months after reopening the dental offices, studies showed that the probability of COVID-19 contamination within dental clinics was very low [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical practice biosafety guidelines, developed during the first year of the pandemic, offer recommendations which guide dental staff in providing safe dental care in the clinical environment. Such recommendations must be updated as new evidence of virus properties arises [68,69]. There is a high level of agreement between different dental specializations about the necessary preventive measures of the routes of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The high risk of virus transmission, together with the existence of asymptomatic patients, forces dentists to consider all patients as potentially infected [ 5 ]. In addition, some health institutions worldwide, such as the National Health Commission (NHC) of the People’s Republic of China, the National Administration of Traditional Chinese Medicine, the Center for Disease Control and Prevention (CDC), The Association of Cantonal Dentists in Switzerland (VKZS) and the Swiss Dental Association (SSO) [ 9 ], the American Dental Association (ADA) [ 10 ], and the World Health Organization (WHO) [ 7 ], have recommended the use of oral antiseptics as agents that can reduce the viral load of SARS-CoV-2 before dental procedures [ 11 ].…”
Section: Introductionmentioning
confidence: 99%